Aerobes and phototrophs as microbial organic fertilizers: Exploring mineralization, fertilization and plant protection features - Wambacq, Eva; Alloul, Abbas; Grunert, Oliver; Carrette, Jasper; Vermeir, Pieter; Spanoghe, Janne; Sakarika, Myrsini; Vlaeminck, Siegfried E.; Haesaert, Geert (PLOS ONE, 2022)
Organic fertilizers and especially microbial biomass, also known as microbial fertilizer, can enable a paradigm shift to the conventional fertilizer-to-food chain, particularly when produced on secondary resources. Microbial fertilizers are already common practice (e.g. Bloom® and Synagro); yet microbial fertilizer blends to align the nutrient release profile to the plant’s needs are, thus far, unexplored. Moreover, most research only focuses on direct fertilization effects without considering added value properties, such as disease prevention. This study has explored three promising types of microbial fertilizers, namely dried biomass from a consortium of aerobic heterotrophic bacteria, a microalga (Arthrospira platensis) and a purple non-sulfur bacterium (Rhodobacter sphaeroides). Mineralization and nitrification experiments showed that the nitrogen mineralization profile can be tuned to the plant’s needs by blending microbial fertilizers, without having toxic ammonium peaks. In a pot trial with perennial ryegrass (Lolium perenne L.), the performance of microbial fertilizers was similar to the reference organic fertilizer, with cumulative dry matter yields of 5.6–6.7 g per pot. This was confirmed in a pot trial with tomato (Solanum lycopersicum L.), showing an average total plant length of 90–99 cm after a growing period of 62 days for the reference organic fertilizer and the microbial fertilizers. Moreover, tomato plants artificially infected with powdery mildew (Oidium neolycopersici), a devastating disease for the horticultural industry, showed reduced disease symptoms when A. platensis was present in the growing medium. These findings strengthen the application potential of this novel class of organic fertilizers in the bioeconomy, with a promising match between nutrient mineralization and plant requirements as well as added value in crop protection.